Prevalence of Ehrlichia canis and Hepatozoon canis in sheltered dogs in southern Aburrá Valley, Colombia - Cabrera-Jaramillo, Azucena; Monsalve, Santiago; Arroyave, Esteban; Rodas, Juan-David (Revista Colombiana de Ciencias Pecuarias, 2022)
Background: Bacteria of the Anaplasmataceae family and canine hemoparasitic protozoans transmitted by ticks are common in Colombia due to circulation and biological adaptation of vector Rhipicephalus sanguineus sensu lato (s.l.). Objective: To detect the circulation of Ehrlichia canis and Hepatozoon canis in sheltered dogs in three municipalities in southern Aburrá Valley, province of Antioquia, Colombia. Methods: Primers were used to amplify the 16S rRNA associated with the Anaplasmataceae family, dsb for Ehrlichia sp. and 18S rRNA for Hepatozoon sp. Results: Of the 357 samples of venous blood obtained, representing all the sheltered dogs in the study zone, Ehrlichia canis DNA was detected in 2.2% of individuals, showing identity of 100% with previous sequences from the GenBank. Hepatozoon canis showed 8.7% (31/357) prevalence of infection, with 100% identity to genotypes from Japan, Brazil, and Spain. Only one sequence of H. canis exhibited a phylogenic divergence concerning H. canis previously reported in Brazil and the Old World. Conclusions: This study confirms the circulation of E. canis and H. canis in asymptomatic shelter dogs in the south-central zone of the Aburrá Valley, province of Antioquia, Colombia. The present study is the first molecular detection of H. canis in the Province of Antioquia and the third report of canine hepatozoonosis from Colombia, highlighting the importance of considering this agent in veterinary clinic.